Samarium-153 labelled microparticles for liver tumour targeted therapy with imaging functionality - Hashikin, N.A.A.; Abdullah, B.J.J.; Ng, K.H.; Chung, L.Y.; Dahalan, R.; Perkins, A.C. (2015)
Samarium-153 (153Sm) are widely used in radia-tion synovectomy and pain management for patients with bone metastases. However, its therapeutic application has not been fully explored. 153Sm has been proven to be useful for imaging purposes. This provides a beneficial alternative for therapy with pure beta emitter especially for liver radioembolization with Yttrium-90 (90Y). This study aimed to develop an alterna-tive radioembolic agent using 153Sm and biocompatible resin microparticles for liver cancer therapy. The ion-exchange resin; Amberlite IR-120 H+ commercially available in large beads were crushed and sieved to 20 – 40 μm and labelled with 152SmCl3 salt prior to neutron activation. Administered activity of 3 GBq 153Sm was aimed based on the standard activity used by the 90Y SIR-Spheres. 6 hours irradiation in 1.494 x 1012 n.cm-2.s-1 flux produced 3.1 GBq.g-1 immediately after activa-tion. Characterization of the microparticles, gamma spectros-copy, and in-vitro radiolabelling studies were carried out and compared to a commercially available resin readily made in 20 – 40 μm, Fractogel EMD SO3- (S). 153Sm-Amberlite micropar-ticles possess a superior and suitable characteristics for liver radioembolization with added imaging capabilities.